2022
DOI: 10.1371/journal.pone.0271119
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam impacts acetyl—And butyrylcholinesterase genes: An epigenetic explanation for postoperative delirium?

Abstract: Midazolam is a widely used short-acting benzodiazepine. However, midazolam is also criticized for its deliriogenic potential. Since delirium is associated with a malfunction of the neurotransmitter acetylcholine, midazolam appears to interfere with its proper metabolism, which can be triggered by epigenetic modifications. Consequently, we tested the hypothesis that midazolam indeed changes the expression and activity of cholinergic genes by acetylcholinesterase assay and qPCR. Furthermore, we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…However, numerous studies have demonstrated that perioperative usage of BZDRAs is linked to a higher risk of POD in geriatric patients with hip fractures ( Poeran et al, 2020 ; Hernandez et al, 2021 ; Duprey et al, 2022 ; Lertkovit et al, 2022 ). The concrete mechanisms of benzodiazepine-induced POD vary based on the subtype of BZDRAs: Diazepam may affect the chloride plasticity mediated by Na + − K + − 2Cl-cotransporter isoform 1 and result in the gamma-aminobutyric acid α receptor malfunction ( Matsumoto et al, 2021 ); midazolam can alter the expression and activity of acetyl-and butyryl-cholinesterase genes ( Rump et al, 2022 ), and both contribute to benzodiazepine - induced POD. Additionally, a retrospective cohort study of 250 patients who were scheduled for surgery under general anesthesia investigated the relationship between the time course of BZDRAs use and the incidence of POD.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…However, numerous studies have demonstrated that perioperative usage of BZDRAs is linked to a higher risk of POD in geriatric patients with hip fractures ( Poeran et al, 2020 ; Hernandez et al, 2021 ; Duprey et al, 2022 ; Lertkovit et al, 2022 ). The concrete mechanisms of benzodiazepine-induced POD vary based on the subtype of BZDRAs: Diazepam may affect the chloride plasticity mediated by Na + − K + − 2Cl-cotransporter isoform 1 and result in the gamma-aminobutyric acid α receptor malfunction ( Matsumoto et al, 2021 ); midazolam can alter the expression and activity of acetyl-and butyryl-cholinesterase genes ( Rump et al, 2022 ), and both contribute to benzodiazepine - induced POD. Additionally, a retrospective cohort study of 250 patients who were scheduled for surgery under general anesthesia investigated the relationship between the time course of BZDRAs use and the incidence of POD.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…[48] Although the effect of midazolam on POD does not appear to be mediated by inflammatory signaling pathways, it may be related to cholinesterase genes. [49] Recently, the use of a new benzodiazepine, remimazolam, was found to reduce the incidence of POD in cardiac surgery. [50] Remimazolam, an ultrashort-acting benzodiazepine, ameliorated the LPS-induced peripheral blood septic response in mice, reduced the number of LPS-induced deaths, and decreased the production of inflammatory factors in cultured macrophages in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, propofol and isoflurane anesthetics were found to unalter the leukocyte DNA methylation according to a recent study [ 33 ], suggesting that more studies are required in this direction to unfold the underlying mechanism behind the role of anesthesia on the surgery-induced DNMT changes and consecutive MCI. However among the five different anesthetics (propofol, sodium thiopental, midazolam, fentanyl, vecuronium) used in the present study for the surgery, three anesthetics propofol [ 34 ], midazolam [ 35 ] and fentanyl [ 36 ] are reported to alter methylation level and its gene expression, therefore this 61% increase in methylation in post-surgical MCI cases may be the cumulative impact of anesthesia and surgery. However, no significant correlation was observed between the specific anesthesia, methylation, and MoCA score in the present study.…”
Section: Discussionmentioning
confidence: 97%